Investigation of the Fe3+ centers in perovskite KMgF3 through a combination of ab initio (density functional theory) and semi-empirical (superposition model) calculations - Emul, Y.; Erbahar, D.; Acikgoz, M. (Amer Inst Physics, 2015)
Analyses of the local crystal and electronic structure in the vicinity of Fe3+ centers in perovskite KMgF3 crystal have been carried out in a comprehensive manner. A combination of density functional theory (DFT) and a semi-empirical superposition model (SPM) is used for a complete analysis of all Fe3+ centers in this study for the first time. Some quantitative information has been derived from the DFT calculations on both the electronic structure and the local geometry around Fe3+ centers. All of the trigonal (K-vacancy case, K-Li substitution case, and normal trigonal Fe3+ center case), FeF5O cluster, and tetragonal (Mg-vacancy and Mg-Li substitution cases) centers have been taken into account based on the previously suggested experimental and theoretical inferences. The collaboration between the experimental data and the results of both DFT and SPM calculations provides us to understand most probable structural model for Fe3+ centers in KMgF3. (C) 2015 AIP Publishing LLC.
Keywords: Field Splitting Parameters; Spin-Hamiltonian Parameters; Tetragonal Fef5o Cluster; Single-Crystals; Epr-Spectra; Resonance; Ions; Pseudopotentials; Distortions; Kznf3